Integrated Strategies: Upaya Meningkatkan Minat Baca Siswa SMA Negeri 1 Sugihwaras Bojonegoro - Fini Siswandari (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
This study aims to determine the level of difference in students' reading interest before and after the implementation of Integrated Strategies. This study uses qualitative descriptive methods. The subject of the study was a student of SMA Negeri 1 Sugihwaras Bojonegoro in the 2019/2020 school year. The results showed an increase in students' reading interest after the implementation of several strategies implemented at SMA Negeri 1 Sugihwaras Bojonegoro.